Exploring the logistics and supply chain services of HIV/AIDS facilities in north-western Nigeria - Kabiru Abubakar Gulma (Elsevier, 2023)
This study aimed to assess the logistics services of HIV/AIDS facilities in the northwestern states of Nigeria, with a particular focus on the National HIV/AIDS Supply Chain Unification Project. The project aimed to streamline the distribution of antiretroviral drugs, HIV rapid test kits, and co-trimoxazole by establishing a coordinated axial storage location for all healthcare facilities providing HIV/AIDS services in Nigeria. A field visit was conducted, covering hospitals under the Supply Chain Unification Project in the Phase 4 region, which includes Jigawa, Kano, Katsina, Kebbi, Sokoto, and Zamfara States. Fourteen (14) assessors visited one hundred and four (104) health facilities comprising thirty-nine (39) providing comprehensive care sites and sixty-nine (69) sites providing Prevention of Mother-To-Child Transmission (PMTCT) services. An adapted Logistics Indicators Assessment Tool (LIAT) was administered. Data were collated and entered into the pre-designed database on Microsoft (MS) Access. The significant gaps identified during this research included inadequately trained personnel, low levels of availability of Standard Operating Procedures (SOP) manuals, a dearth of firefighting gadgets, and non-use of Personal Computers (PCs) and internet availability for transmission of reports. All these require urgent attention from stakeholders in most of the sites visited. Findings were documented, with follow-up actions to be implemented as appropriate. Findings and recommendations have been communicated to the government, implementing partners, and sub-recipients supporting the facilities. It is expected that the findings from these visits will be used in developing appropriate solutions/next steps to improve the HIV/AIDS commodities supply chain management in the country.